2007
DOI: 10.1007/s00436-007-0677-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among Trichinella pseudospiralis isolates from Australian, Nearctic, and Palearctic regions

Abstract: The study of the genetic polymorphism of pathogens is important for phylogenetic and biogeographic studies and, in the case of foodborne pathogens, to trace the origin of food infection. Since its discovery in 1972, the nonencapsulated species Trichinella pseudospiralis has been detected in mammals and birds, and human infection has occurred, in some cases resulting in death. We studied DNA polymorphism among ten T. pseudospiralis isolates from the Palearctic, Nearctic, and Australian regions, screening the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Furthermore, these two genotypes can be easily distinguished among them by a PCR-RFLP analysis of this sequence with the ApalI restriction enzyme. Wu et al (2007) studied the genetic relationships among T. pseudospiralis isolates from Australia, Nearctic, and Palearctic regions. They demonstrated that the Palearctic population (seven isolates from six different hosts from four European and two Asian countries) consisted of a uniform genotype suggesting that there is a frequent gene flow among the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these two genotypes can be easily distinguished among them by a PCR-RFLP analysis of this sequence with the ApalI restriction enzyme. Wu et al (2007) studied the genetic relationships among T. pseudospiralis isolates from Australia, Nearctic, and Palearctic regions. They demonstrated that the Palearctic population (seven isolates from six different hosts from four European and two Asian countries) consisted of a uniform genotype suggesting that there is a frequent gene flow among the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of phylogenetic relationships among the known cyanases (Figure 2) provided evidence for a common evolutionary origin for plant cyanases. It is suggested that the conserved cyanases are derived from an ancient gene, which makes it possible to study inter- and intra-specific relationships using cyanase as a phylogenetic marker [28]. The high resolution crystal structure of E. coli cyanase explains the structural and kinetic properties of the enzyme: the active enzyme is a homodecamer composed of five inactive dimmers, and catalytic residues were identified [8].…”
Section: Discussionmentioning
confidence: 99%
“…Total genomic DNA was also isolated from T. pseudospiralis (code ISS13), T. spiralis (ISS004) and T. britovi (ISS1088) reference strains, maintained in laboratory mice. In addition, samples of DNA from four geographically related T. pseudospiralis isolates previously used in the study of Wu et al (2007) were kindly provided by Dr. Vilam Šnábel. Of these, three isolates were stated as reference samples characterized by code number and locality, namely ISS1348 (Sweden), ISS1432 (Slovakia), ISS141 (Australia-Tasmania) and one non-reference isolate from Finland.…”
Section: Isolation Of Dna and Polymerase Chain Reactionsmentioning
confidence: 99%
“…After electrophoresis, an approximately 419 bp band, previously characterized by a high variability among T. pseudospiralis isolates (La Rosa et al 2001;Wu et al 2007) was subjected to RFLP analysis (restriction fragment length polymorphism) with restriction endonuclease RsaI Fast digest (Fermentas) according to the manufacturer´s instructions. PCR products for above mentioned isolates were purified using NucleoSpin Gel and PCR Clean-up Kit (Machery-Nagel, Germany).…”
Section: Rflp Analysis Of Coi Genementioning
confidence: 99%